Introduction [in Ghana’s economic and agricultural transformation] - Diao, Xinshen; Hazell, Peter B. R.; Kolavalli, Shashidhara; Resnick, Danielle (International Food Policy Research Institute, 2019)
Why have African economies developed in this way and why has industrialization been so difficult to achieve? And if industrialization is going to be difficult to achieve for African countries, what viable policy options exist to generate sustainable structural transformations in the region? To tackle these important questions in a tractable manner, this book focuses on the experience of one country—Ghana—and examines the country’s overall economic performance since it went through a major Structural Adjustment Program (SAP) in the early 1980s and provides a detailed analysis of the performance of the agricultural sector. In so doing, the book aims to explain why Ghana has not transformed its economy more substantially, why its agriculture sector— beyond cocoa—has not played a greater role, and what it must do in the future if it is to continue with a successful transformation. Addressing these puzzles requires integrating economic and political analyses. Finally, the book considers what the rest of Africa can learn from Ghana’s experience.